Saurauia speciosa - Hoo, P.K.; Colin Ruzelion Maycock; Damit, A.; Khoo, E.; Nilus, R.; Sugau, J.; Tanggaraju, S.; Tsen, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Saurauia speciosa is endemic to Sabah where it is relatively widespread. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 48 km2 and 22,858 km2, respectively. As it is a lowland species, it is threatened by land use change, leading to an estimated decline of 50% in AOO and 4% in EOO. It is found in 11 locations, all of which are within Totally Protected Areas (TPAs) but potential disturbance is still a threat to each locality. It has an ability to adapt to secondary forests and different soil type. It is assessed as Near Threatened nearly meeting threatened category under criterion B. Saurauia speciosa is endemic to Sabah, Malaysia. It is restricted to west and east Sabah.